THE EFFECT OF SELF-EQUILIBRATING STRESSES DUE TO MULTI-LINE SPOT WELDED STIFFENERS ON THE NATURAL FREQUENCIES OF PLATE (Journal of Engineering, 2009)
In this paper an investigation has been made into the effect of residual stresses on the vibration characteristics of a thin rectangular stainless steel plate with multi-line spot welded stiffeners. A new general frequency equation with and without the effect of residual stresses due to multi-line spot welding along the length and width of the plate for different boundary conditions were obtained. The results give that the free ends tries to increase the natural frequencies while the clamped edges try to decrease the natural frequencies; also the central position weld line has the great influence on the natural frequencies.